Rasch stacking analysis: differences in student resilience in terms of gender - Ifdil, Ifdil; Fadli, Rima Pratiwi; Syahputra, Yuda; Erwinda, Lira; Zola, Nilma; Afdal, Afdal (Konselor, 2018)
West Sumatra as one of the zones in Sumatra that has high natural disasters. Improving self-resilience from natural disasters are needed, so it is necessary to describe the condition of student resilience after the disaster so far. This study aims to describe the differences in resilience between male and female students in high school in West Sumatra. The sample from this study was 802 students (406 men and 396 women) spread in secondary schools in West Sumatra. The analysis technique used is independent sample t-test combined with stacked rash models. The results of the analysis show that there are differences in resilience between male female students in high school in West. The female students higher than that of male, which is seen from the female to higherÂ  than male in answering the TIRI instrument.